조직구성원의 외재적, 내재적 동기와 창의성의 관계: 조건적 보상의 조절효과 - 황소연(Soyeon Hwang); 정혜정(Heajung Jung) (International journal of industrial distribution and business, 2018)
Purpose - This study examined the effects of intrinsic and extrinsic motivation on employee creativity. Past research has consistently shown that intrinsic motivation is positively related to creativity. Yet conflicting results have been reported about the relationship between extrinsic motivation and creativity. To explore the reason why extrinsic motivation can either help or hurt creativity, we examined the role of contingent rewards as a moderator and tested whether either tangible or intangible rewards contingent upon creative performance significantly impact the relationship between extrinsic motivation and creativity. Research design, data, and methodology - Survey data was collected from employees working for diverse organizations in Korea through online research firm. Only employees who reported their job or organization provided opportunities to use their creativity were allowed to continue the survey. Out of 305 initial responses collected, those with too much missing data were deleted, which finally left 278 responses for statistical analyses. To examine the validity of the measurements, confirmatory factor analysis was first conducted. Next, to test the hypothesized relationships, multiple hierarchical regression analyses were conducted. Results - As hypothesized, both intrinsic and extrinsic motivation had positive effects on creativity. It was shown that contingent rewards did not influence the positive relationship between intrinsic motivation and creativity, but did significantly moderate the relationship between extrinsic motivation and creativity in a way that tangible rewards strengthened the relationship while intangible rewards mitigated the same relationship. Conclusions - This research enhances our understanding on the relationship between motivation type, rewards, and creativity. Intrinsically motivated employees showed a high level of creativity regardless of whether rewards were expected or not. In contrast, extrinsically motivated employees showed more or less creative behavior depending on whether they were expected to have tangible or intangible rewards. As extrinsic motivation is typically associated with tangible rewards such as pay, promotion, etc., tangible rewards were seen to be more effective in promoting creative performance from extrinsically motivated employees than intangible rewards. Our findings make a significant theoretical contribution to reconcile prior inconsistent findings. Furthermore, they provide useful insights for managers and organizations into developing effective strategies for facilitating employee creativity.